2006
DOI: 10.1590/s0103-97332006000300004
|View full text |Cite
|
Sign up to set email alerts
|

Variable range hopping conduction in low-temperature molecular beam epitaxy GaAs

Abstract: Electric transport properties measured by Van der Pauw resistivity experiments of Low-Temperature Molecular Beam Epitaxy (LT-MBE) GaAs samples are used to identify a method to improve the resistivity of GaAs material. We present results on five samples grown at 265, 310, 315, 325, and 345 o C. The electric measurements were carried out at temperatures ranging from 130 to 300 K. In this temperature range the dominant transport process is identified as variable range hopping. The hopping parameter plotted agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Chaudhuri et al [27] observed the VRH mechanism in n-type GaAs below 40 K. But Rodriguez et al [28] observed the VRH mechanism in CuInTe 2 in the temperature range 53-95 K, a relatively high temperature range. Rubinger et al [29] observed the VRH mechanism at even higher temperatures, 130-300 K, in semiconducting GaAs prepared by molecular beam epitaxy.…”
Section: Resultsmentioning
confidence: 99%
“…Chaudhuri et al [27] observed the VRH mechanism in n-type GaAs below 40 K. But Rodriguez et al [28] observed the VRH mechanism in CuInTe 2 in the temperature range 53-95 K, a relatively high temperature range. Rubinger et al [29] observed the VRH mechanism at even higher temperatures, 130-300 K, in semiconducting GaAs prepared by molecular beam epitaxy.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature dependence of the electric resistivity ρ indicated the semiconductor-like behavior as shown in Figure , that is, ρ was increased with decreasing temperature, and the magnitude of ρ at room temperature (ρ RT ) showed a tendency to decrease with increasing the boron concentration in the composite rod for the sample preparation (see inset in Figure ). The latter tendency can be considered as a result of increasing the metallic character of individual MWNTs, and the mechanism of the former temperature dependence can be explained by the Mott's variable range hopping (VRH) conduction, which is frequently seen in the assembly of the small conducting materials or particles.
1 Temperature dependence of the electric resistivity ρ for the pellet-formed MWNTs. Explanation of the sample codes (B0NT, B5NT, and so on) is in the text.
…”
Section: Resultsmentioning
confidence: 99%